Enhancement of ferroelectric and ferromagnetic properties of Gadolinium (Gd) and Nickel (Ni) co-doped BiFeO3. Issue 11 (1st August 2020) - Mai Oanh, Le Thi; Thang, Dao Viet; Bich, Do Danh; Chung, Pham Do; Hung, Nguyen Manh; Van Quang, Nguyen; Van Minh, Nguyen
Abstract: The structural, vibrational, optical, ferroelectric, and ferromagnetic properties of single phase BiFeO3 (BFO) and Bi1- x Gdx Fe0.975 Ni0.025 O3 ( x 0.00, 0.025, 0.05, 0.075, 0.10, 0.125, and 0.15) materials, synthesized by sol-gel method have been investigated systematically using different techniques. X-ray diffraction patterns (XRD) revealed that all samples crystallized in single phase and showed a compressive lattice distortion with increasing Gd-doping concentration. A structural phase transition from rhombohedral to orthorhombic took place at co-doped sample with x = 0.125 which was evidenced by both XRD analyses and Raman scattering spectra. Optical band gap was slightly decreased with Gd-doping content. Ni and Gd co-substitution in BFO caused a remarkable enhancement of both ferroelectric and ferromagnetic properties which was demonstrated by the sharp increasing of maximum ( P s ) and remnant ( P r ) polarization, dielectric constant ( ε ), saturation ( M s ) and remnant ( M r ) magnetization. Our results indicated the effective contributions of Ni-doping and Gd-doping in the innovations of ferromagnetism and ferroelectricity of BFO, respectively.